Food and nutrition knowledge, attitudes and practices among children in public primary school with canteens in southern Benin: A case study - Bello, Faïck; Koukou, Elie; Bodjrenou, Sam; Termote, Céline; Azokpota, Paulin; Hounkpatin, Waliou Amoussa (BioMed Central, 2024)
Abstract Background Food and nutrition notion among schoolchildren in Benin is still less documented. Few studies have examined the determinants of food and nutrition among schoolchildren while others have attempted to link knowledge, attitudes and practices to diet. The present study aims to evaluate food and nutrition knowledge, attitudes and practices among schoolchildren enrolled in public primary schools canteens in Cotonou and its surroundings. Methods A diagnostic study was conducted in twelve public primary schools with canteens. A structured interview questionnaire was used to collect data from 861 schoolchildren aged 7 to 14 years. Three scores were used to assess the level of knowledge, attitude and practice. The overall score was the total of correct responses. The maximum score for all the three parameters was 15, 6 and 4 respectively for knowledge, attitude and practices. Data were analyzed using STATA 16. Logistic regression was performed to identify the relationship between food and nutrition practices and knowledge and attitude. Pearson goodness of fit test was performed to verify the adequacy of the model. A P-value of less than 0.05 ( P < 0.05) was considered significant at 95% confidence interval. Results schoolchildren’s nutrition knowledge was low (mean score 2.52 ± 1.33) while attitude and practices were acceptable (mean score 4.08 ± 1.39 and 2.84 ± 0.77). Only 18.2% of schoolchildren knew the different food groups and 3.4% knew that they should eat at least five fruits and vegetables a day. Most of the schoolchildren (93.6%) were favorable to eat at least five fruits and vegetables and 86.8% were willing to eat more than 3 times a day. Among all practices, snacking between meals and eating breakfast were poorly observed by the schoolchildren. Nutrition knowledge was associated with practices observed among schoolchildren but not with attitudes. However, a significant positive association was observed ( p < 0.05) between attitudes and practices. Conclusion Knowledge on food and nutrition among schoolchildren from public primary schools with canteen was low. This study suggests implementation of nutritional education to improve schoolchildren’s knowledge and attitudes towards healthy diets and nutrition.